2020
DOI: 10.1155/2020/1753964
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Design of the Sealing Structure of a Hydraulic Cylinder on the Basis of a Surrogate Model

Abstract: In this study, a finite-element simulation model was established for a two-dimensional hydraulic cylinder seal structure with highly nonlinear materials and contacts for achieving the optimal sealing effect with the structure. The effects of gaps as well as single and double O-rings on the sealing effect were examined. On the basis of this examination, a parametric model was developed for double-O-rings without gaps, which are suitable for hydraulic cylinder sealing. Suitable design variables, objective functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Subsequently, the sealing performance of rubber O-rings under the action of high-pressure hydrogen was discussed, including static sealing characteristics and dynamic sealing characteristics. Hong Zhang and Zhen Li [17,18] established a structural simulation model to analyze the influence of different structural parameters on the sealing performance of O-rings to achieve the best sealing effect of the structure.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the sealing performance of rubber O-rings under the action of high-pressure hydrogen was discussed, including static sealing characteristics and dynamic sealing characteristics. Hong Zhang and Zhen Li [17,18] established a structural simulation model to analyze the influence of different structural parameters on the sealing performance of O-rings to achieve the best sealing effect of the structure.…”
Section: Introductionmentioning
confidence: 99%
“…Wei et al (2020) investigated the sealing characteristics of aircraft Glacis rings under 21 MPa operating conditions, and the results showed that the friction force gradually increased with the increase of fluid pressure; the friction force increased significantly with the increase of temperature. Yan et al (2020) considered the amplitude and wavelength of surface roughness and analyzed the effects of ACGT-type seal motion velocity and hydraulic oil viscosity variation on the lubrication performance and sealing performance of the seal. Zhang et al (2021) and Zhang and Li (2021) conducted numerical analysis and finite element simulation research on the main seal of aviation actuators, established a mixed lubrication model for reciprocating seals, calculated the friction force and reverse pump return rate of the reciprocating seal system and provided a reference basis for the structural optimization of reciprocating seals.…”
Section: Introductionmentioning
confidence: 99%